The effect of a video-based vs. real-life setting on the visual and motor behaviour in the return to service in tennis and wheelchair tennis - R. Reina; F. J. Moreno; D. Sanz; J. S. Damas; V. Luis (Asociación Española de Ciencias del Deporte, 2010)
The study of the visual and motor behaviour in a simulated situation of return to service in tennis and wheelchair tennis was carried out, where participants responded to the serves in both real-life (3D) and video-based settings (2D). Automated systems to acquire data were employed, trying to simulate the attentional demands of the game in the video-based situation. Three groups were analysed in the study: a novice wheelchair tennis players, experienced wheelers, and a group of non-disabled tennis players. They observed two series (2D and 3D) of 24 top-spin services, performed by two wheelchair tennis players and other two players in a biped position. Participants showed a higher number of visual fixations in the video-based situation, as well as a higher number and time of visual fixation on locations of the upper body. On the other hand, in the real-life setting, they showed a higher number and time of visual fixation on the ball. According to the results, it seems that a lesser familiarization with the video-based situation could modify the visual search strategy, especially in the pursuit of the trajectory of the ball. KEY WORDS: Dimensionality, Visual behaviour, Reaction response, Wheelchair tennis, Tennis, Return to service